Defining critical roles for NF‐κB p65 and type I interferon in innate immunity to rhinovirus - Nathan W. Bartlett; Louise Slater; Nicholas Glanville; Jennifer J. Haas; Gaetano Caramori; Paolo Casolari; Deborah L. Clarke; Simon D. Message; Julia Aniscenko; Tatiana Kebadze; Jie Zhu; Patrick Mallia; et al. (EMBO Molecular Medicine)
Abstract The importance of NF‐κB activation and deficient anti‐viral interferon induction in the pathogenesis of rhinovirus‐induced asthma exacerbations is poorly understood. We provide the first in vivo evidence in man and mouse that rhinovirus infection enhanced bronchial epithelial cell NF‐κB p65 nuclear expression, NF‐κB p65 DNA binding in lung tissue and NF‐κB‐regulated airway inflammation. In vitro inhibition of NF‐κB reduced rhinovirus‐induced pro‐inflammatory cytokines but did not affect type I/III interferon induction. Rhinovirus‐infected p65‐deficient mice exhibited reduced neutrophilic inflammation, yet interferon induction, antiviral responses and virus loads were unaffected, indicating that NF‐κB p65 is required for pro‐inflammatory responses, but redundant in interferon induction by rhinoviruses in vivo. Conversely, IFNAR1−/− mice exhibited enhanced neutrophilic inflammation with impaired antiviral immunity and increased rhinovirus replication, demonstrating that interferon signalling was critical to antiviral immunity. We thus provide new mechanistic insights into rhinovirus infection and demonstrate the therapeutic potential of targeting NF‐κB p65 (to suppress inflammation but preserve anti‐viral immunity) and type I IFN signalling (to enhance deficient anti‐viral immunity) to treat rhinovirus‐induced exacerbations of airway diseases. See accompanying article http://dx.doi.org/10.1002/emmm.201202032